Propuesta de automatización de prueba de control de calidad de producto terminado en la empresa DAVMOTOR CÍA. LTDA. - Aragón Pilco, Bryan Jair (2020)
The present proposed technological is focused on the development and creation of a measurement system that allows to detect the vibrations produced at strategic points of the bodywork in interprovincial units, which due to the lack of historical data were chosen through a survey applied to the quality supervisor of the company DavMotor Cía. Ltda., The finality of the proposal is that the internal quality control process generates quantitative and qualitative values with respect to the finished product. The development of the proposal is necessary due to the high rate of interprovincial units that return to the industrial plant through a process of readjustment of failures covered by manufacturing guarantees, which in the year 2019 amounts to 42% and is carried out through a explanatory research with a quantitative and qualitative approach. Piezoelectric sensors and XBee radiofrequency modules are used for the measurement system to transmit the information, all these components are based on the IEEE 802.15.4 standard. To create a multipoint network with the help of the XCTU software, the information is processed by the Arduino UNO board and displayed in a graphical interface that allows the measurement system history to be saved in an XLS file extension. The development of constant tests allowed to determine the control limit for the strategic measurement points, for a reference measurement (LCS), in the same way a test was developed with the proposal presented in an interprovincial unit, with the help of a programming in Excel generated the first report detailing the behavior of the measurement points, therefore the impact that this first test had on the quality department was measured with the proposed measurement system, resulting in a positive acceptance of the Proposal presented with respect to the current process, the project will provide traceability on the process of internal quality control and thus help future decision making.